Profil Ketrampilan Berpikir Kreatif Konsep Nanotechnologi Menggunakan Model Problem Base Learning pada Siswa SMA - Samuji Samuji; Joko Siswanto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
This study aims to describe the profile of creative thinking ability of class X students of SMA 3 Pemalang on atomic structure material and periodic tables of chemistry subjects in the 2019/2020 academic year. The research subjects were 36 students of class X SMA 3 Pemalang. The research method used is the quantitative descriptive method. Retrieval of data using essay test questions which were then announced about indicators of students' creative thinking abilities. The creative thinking ability of SMA 3 Pemalang students is 12.44 (38.89%) of the maximum score of 32. If viewed from the ability of students based on indicators of Fluency 1.5 (37.50%), Flexibility 1.71 (42.71%), Originality 1.47 (36.81%), Elaboration 1.54 (38.54%).